Analysis of Technological Pedagogical Content Knowledge Competence of Biology Teachers in the Use of High School Instructional Media - Harlis; Retni Sulistiyoning Budiarti; Dara Mutiara Aswan; Hendra Budiono (Postgraduate, University of Mataram, 2024)
This study aims to analyze the Technological Pedagogical Content Knowledge (TPACK) competence of biology teachers in the use of instructional media in high schools in Kuala Tungkal. This research employs a descriptive method with a quantitative approach, involving 7 biology teachers from 3 public high schools in Kuala Tungkal as subjects. Data were collected through questionnaires, interviews, and observations. The results indicate that the technology-based instructional media used by teachers vary according to the needs of the materials being taught. In terms of technological knowledge, the average percentage obtained was 77.78%, which falls under the Good category, while the pedagogical content knowledge aspect scored an average percentage of 84.4%, categorized as Very Good. The conclusion of this study suggests that biology teachers in Kuala Tungkal have good TPACK competence in the use of instructional media. Recommendations from this study include the enhancement of training for developing more advanced technology-based instructional media, such as e-modules and interactive simulations, to further improve the quality of biology education.